Mass Arrests of Women’s Rights Defenders - Human Rights Watch (Human Rights Watch, 2023)
Iranian authorities have arrested at least a dozen activists and increased pressure on a wide range of peaceful dissidents ahead of the anniversary of the nationwide protests that swept the country in 2022.
Keywords: 2023-08 August